Recueil des avis de classement = Compendium of classification opinions (The Organization BrusselsBE, 2012)
Consists of a list, set out in the order of the headings and subheadings of the Harmonized Description and Coding System of the classification opinions adopted by the Customs Co-operation Council.
On permanent loan to Single Market and Economy Sub-Programme (Mr. Breedy, Mr. Black, Mr. Watson).